Technical advances in surgery for pancreatic cancer - Schneider, Martin; Hackert, Thilo; Strobel, Oliver; Büchler, Markus W. (The British journal of surgery, 2021)
Multimodal treatment concepts enhance options for surgery in locally advanced pancreatic ductal adenocarcinoma (PDAC). This review provides an overview of technical advances to facilitate curative-intent resection in PDAC.A review of the literature addressing current technical advances in surgery for PDAC was performed, and current state-of-the-art surgical techniques summarized.Artery-first and uncinate-first approaches, dissection of the anatomical triangle between the coeliac and superior mesenteric arteries and the portomesenteric vein, and radical antegrade modular pancreatosplenectomy were introduced to enhance the completeness of resection and reduce the risk of local recurrence. Elaborated techniques for resection and reconstruction of the mesenteric-portal vein axis and a venous bypass graft-first approach frequently allow resection of PDAC with venous involvement, even in patients with portal venous congestion and cavernous transformation. Arterial involvement does not preclude surgical resection per se, but may become surgically manageable with recent techniques of arterial divestment or arterial resection following neoadjuvant treatment.Advanced techniques of surgical resection and vessel reconstruction provide a toolkit for curative-intent surgery in borderline resectable and locally advanced PDAC. Effects of these surgical approaches on overall survival remain to be proven with high-level clinical evidence.
Gesehen am 09.05.2022